2023
DOI: 10.3389/fpain.2023.1038808
|View full text |Cite
|
Sign up to set email alerts
|

The degeneration-pain relationship in the temporomandibular joint: Current understandings and rodent models

Abstract: Temporomandibular disorders (TMD) represent a group of musculoskeletal conditions involving the temporomandibular joints (TMJ), the masticatory muscles and associated structures. Painful TMD are highly prevalent and conditions afflict 4% of US adults annually. TMD include heterogenous musculoskeletal pain conditions, such as myalgia, arthralgia, and myofascial pain. A subpopulations of TMD patients show structural changes in TMJ, including disc displacement or degenerative joint diseases (DJD). DJD is a slowly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 165 publications
1
5
0
Order By: Relevance
“…Animal models mimicking the high levels of inflammation observed in the TMJ of TMD patients have been developed using direct injection of chemical agents, including complete Freund’s adjuvant (CFA), zymosan, carrageenan, mustard oil, monoiodoacetate, albumin, and formalin, into the TMJ to cause inflammation. It has been confirmed that intra-TMJ injections of CFA cause mechanical hyperalgesia within the TMJ in rodents[9]. Consistent with this, we confirmed hypersensitivity lasting up to 7 days in the V3 region of CFA-injected mice by the von Frey test (Fig.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Animal models mimicking the high levels of inflammation observed in the TMJ of TMD patients have been developed using direct injection of chemical agents, including complete Freund’s adjuvant (CFA), zymosan, carrageenan, mustard oil, monoiodoacetate, albumin, and formalin, into the TMJ to cause inflammation. It has been confirmed that intra-TMJ injections of CFA cause mechanical hyperalgesia within the TMJ in rodents[9]. Consistent with this, we confirmed hypersensitivity lasting up to 7 days in the V3 region of CFA-injected mice by the von Frey test (Fig.…”
Section: Resultssupporting
confidence: 90%
“…While CFA can induce acute inflammatory reactions and histological modifications in the TMJ, including extracellular matrix accumulation and soft tissue alterations, CFA does not cause cartilage and bone degradation. Furthermore, this model is not fully representative of the underlying causes driving the sustained pain and degeneration experienced by human patients, as it does not encompass the unidentified foundational elements contributing to the persistence of these conditions [9]. Because excessive TMJ activity and prolonged mouth opening are risk factors in development of TMD [6], the FMO model of TMD-related pain is attractive [15,33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TMD can affect up to 70% of the population with most of them being young patients. 12 Classic subpopulations of TMD are known as myofascial, disc displacement with or without reduction, and degenerative joint disease 13 . TMD can be caused by trauma, bruxism, malocclusion, and TMJ disk dislocation 11 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…TMD is primarily characterized by musculoskeletal pain syndromes which comprise myofascial pain, myalgia, and arthralgia. [ 2 ]. The etiology of TMD is not fully understood; however, it is believed to involve a combination of biological, environmental, social, emotional, and cognitive factors.…”
Section: Introductionmentioning
confidence: 99%